Detergent-compatible, organic solvent-tolerant alkaline protease from Bacillus circulans MTCC 7942: Purification and characterization. Issue 1 (2nd January 2016) - Patil, Ulhas; Mokashe, Narendra; Chaudhari, Ambalal
ABSTRACT: Proteases are now recognized as the most indispensable industrial biocatalyst owing to their diverse microbial sources and innovative applications. In the present investigation, a thermostable, organic solvent-tolerant, alkaline serine protease from Bacillus circulans MTCC 7942, was purified and characterized. The protease was purified to 37-fold by a three-step purification scheme with 39% recovery. The optimum pH and temperature for protease was 10 and 60°C, respectively. The apparent molecular mass of the purified enzyme was 43 kD as revealed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The Km and Vmax values using casein-substrate were 3.1 mg/mL and 1.8 µmol/min, respectively. The protease remained stable in the presence of organic solvents with higher (>3.2) log P value (cyclohexane, n -octane, n -hexadecane, n -decane, and n -dodecane), as compared to organic solvents with lower (<3.2) log P value (acetone, butanol, benzene, chloroform, toluene). Remarkably, the protease showed profound stability even in the presence of organic solvents with less log P values (glycerol, dimethyl sulfate [DMSO], p -xylene), indicating the possibility of nonaqueous enzymatic applications. Also, protease activity was improved in the presence of metal ions (Ca 2+, Mg 2+, Mn 2+ ); enhanced by biosurfactants; hardly affected by bleaching agents, oxidizing agents, and chemical surfactants; and stable in commercial detergents. In addition, a protease–detergent formulation effectively washed out egg and blood stains as compared to detergent alone. The protease was suitable for various commercial applications like processing of gelatinous film and as a compatible additive to detergent formulation with its operative utility in hard water.